Anti-Ulcer Effects of Piper Betel, Solanum Nigrum and Zingibercassumunar on Ulceration Induced by Selected Ulcerogens Inrats - Abdul Rahman, Shamima (2005)
Piper betel, Solanum nigrum and Zingiber cassumunar have been used among Malay community in traditional medicine for curing many diseases. These plants are believed to protect the mucosal lining of the stomach from ulcerogens. This study was conducted to investigate the antiulcerogenic properties of ethanol extracts of these plants. One hundred and forty four Sprague Dawley rats were used in this study. The rats were divided into two major groups, the control and treatment group. There were 6 groups of control rats (normal saline (Al); ethanol (Bl); aspirin (Cl); acetic acid (Dl); indomethacin (El); and cimetidine (Fl)). All control groups received distilled water ad libitum 7 days and fasted 24 hours prior forced fed either with normal saline, ethanol, aspirin, acetic acid, indomethacin and cimetidine accordingly. Treated groups were given 2mg / lOOg body weight per day of Piper betel, Solanum nigrum and Zingiber cassumunar extract for 7 days, fasted 24 hours prior force fed with either normal saline (Group A2, A3, A4); ethanol (Group B2, B3, B4); aspirin (Group C2, C3, C4); acetic acid (Group D2, D3, D4); indomethacin (Group E2, E3, E4) or cimetidine (Group F2, F3, F4) accordingly. They were 18 groups all together. They were then fasted again for 24 hours before sacrificed. Macroscopically, the stomachs of rats treated with all plant extracts of all ulcerogen groups (B2, B3, B4; C2, C3, C4; D2, D3, D4; E2, E3, E4; F2, F3, F4) showed a reduced ulcers with significant different (p < 0.05) when compared to B1, C1, Dl and El control groups. Even though treated groups showed some edema and small ulcers, they gave less lesion score when compared to B1, Cl, Dl and El control group. Histological findings showed reduced damage and inflammation score without erosion of mucosal layer in groups treated with Piper betel, Solanum nigrum and Zingiber cassumunar when compared to B1, C1, Dl and El groups. Even though there was slight epithelial disruptions, minimal inflammatory reactions and presence of red blood cells, the damage and inflammation score were less and significantly reduced (p < 0.05) when compared to control groups. This present study suggests that Piper betel, Solanum nigrum and Zingiber cassumunar have some beneficial properties implying that they may have some protective mechanisms to protect stomach from ulcerogens.